She's leaving home: A large sample investigation of the empty nest syndrome - Alan Piper; Ian Jackson (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This study considers life satisfaction in relation to the empty nest syndrome, which is a situation where there are feelings of loss or loneliness for mothers and/or fathers following the departure of the last child from the parental home. In particular, the investigation considers the significance of Identity Economics when applied to parents experiencing a reduction in well-being following an extended period of child-rearing. The origins of the empty nest syndrome are first considered briefly before conducting an economic analysis of life satisfaction using the German Socio-Economic Panel. Our particular focus is the change in the subjective well-being of the individuals who become empty nesters, taking advantage of the richness of this dataset. As a result, this is the first large sample economic analysis of its kind to use identity to evaluate the effects of becoming "empty nest" parents in a systematic way.
Keywords: D64; I31; 330